1981
DOI: 10.1113/expphysiol.1981.sp002541
|View full text |Cite
|
Sign up to set email alerts
|

A Horseradish Peroxidase Study of Vagal Motoneurones With Axons in Cardiac and Pulmonary Branches of the Cat and Dog

Abstract: SUMMARYThe location, within the brain stem, of vagal efferent neurones with axons in the cardiac and pulmonary branches of the cat, and the cardiac branch of the dog, have been defined. Horseradish peroxidase was applied to the cut central ends of these vagal branches and, after an appropriate time, sections of the brain stem were examined for labelled cell bodies. Labelled cell bodies were found ipsilaterally in the dorsal motor vagal nucleus, the nucleus ambiguus and in the reticular formation between these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

1984
1984
2002
2002

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 24 publications
4
32
0
2
Order By: Relevance
“…It is generally accepted (La Vail & La Vail, 1974;Ellison & Clarke, 1975;Schramm, Adair, Stribling & Gray, 1975;Kristensson, 1978;Bennett et al 1981) that retrograde transport of horseradish peroxidase occurs at rates faster than 3-5 mm.h-1. The maximum transport distances involved in our experiments were 4 cm and 2 cm for the dog and cat respectively and even with the shortest elapsed time neurones much further rostral and caudal to those observed could have been labelled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted (La Vail & La Vail, 1974;Ellison & Clarke, 1975;Schramm, Adair, Stribling & Gray, 1975;Kristensson, 1978;Bennett et al 1981) that retrograde transport of horseradish peroxidase occurs at rates faster than 3-5 mm.h-1. The maximum transport distances involved in our experiments were 4 cm and 2 cm for the dog and cat respectively and even with the shortest elapsed time neurones much further rostral and caudal to those observed could have been labelled.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were incubated for the demonstration of horseradish peroxidase labelled cells by a modified p-phenylenediamine pyrocatechol technique (Hanker, Yates, Metz & Rustioni, 1977;Bennett, Kidd, Latif & McWilliam, 1981) or by the tetramethyl benzidine method (Mesulam, 1978). They were air dried onto slides, cleared and mounted for examination using bright-and dark-field light microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Ciriello & Calaresu (1979, however, claim a segregation of c.v.m.s, first, on the basis of location (dorsal vagal nucleus and nucleus ambiguus) and, secondly, as to whether they receive only one or convergent excitatory inputs from both sinus and aortic nerves. We do not eliminate the possibility of c.v.m.s being found on occasions in the dorsal vagal nucleus in the cat although we believe that the majority are located in the nucleus ambiguus (see also Bennett et al 1981) but whenever tested these c.v.m.s were shown to receive convergent inputs from both the sinus and aortic nerves. A segregation on the basis of input has also been challenged in experiments on rats (Nosaka, Yasunaga & Tamai, 1982).…”
Section: P Gilbey and Othersmentioning
confidence: 99%
“…The present results are not inconsistent with such a hypothesis. However, it was suggested that the pulmonary C fibre-evoked bradyeardia could involve vagal nonmyelinated preganglionic fibres with their cells in the dorsal vagal motor nucleus of the cat (Bennett et al 1981;Donoghue, Fox, Kidd & Koley, 1981;Bennett, Ford, Kidd & McWilliam, 1984;Jordan, Spyer, Withington-Wray & Wood, 1986). These neurones are cardioinhibitory in function (Woolley, McWilliam, Ford & Clarke, 1987) and can be activated synaptically by electrical stimulation of non-myelinated pulmonary vagal afferents (Bennett, Goodehild, Kidd & MeWilliam, 1985) but not by lung inflation (Bennett et al 1984).…”
Section: Possible Mechanisms Of Respiratory Modulationmentioning
confidence: 99%